Uma experiência de corrosão metálica em meio ácido - Vaz, Ednilson L. S. [UNESP]; Codaro, Eduardo N. [UNESP]; Acciari, Heloisa Andréa [UNESP] (My University, 2013)
In this paper it is proposed a method to characterize the corrosion reactions of many metals and alloys in acid media and to evaluate the corrosion rate. An alloy of aluminum and zinc was partially dissolved in HCl solution and the medium acidity decrease was monitored at different time intervals by using a pHmeter. Data analysis and physical chemistry treatment permitted associate the pH increase with the alloy mass loss. This proposal promotes learning of terminology and concepts involved as well as contribute to better understand the corrosion phenomena.
An experience of metallic corrosion in acidic medium
Keywords: Aluminum alloys; Chemistry education; Generalized corrosion